Optimization of supercritical fluid extraction of asiaticoside from Centella asiatica using Central Composite Design (CCD). Issue 16 (2nd November 2021) - Ruslan, Fatin Shazwani; Susanti, Deny; Taher, Muhammad; Mohammad, Nurul Farahain
ABSTRACT: The extraction of asiaticoside was performed using supercritical fluid extraction to produce highly concentrated extracts. The effects of three factors (co-solvent percentage, pressure, and temperature) on the asiaticoside content were screened using the Two-Level Factorial design and optimized using the Central Composite Design. Asiaticoside was extracted following the treatment combinations of three parameters, namely co-solvent (5–15%), temperature (70–90°C), and pressure (1–20 MPa). The optimized extraction parameters were identified at 10%, 10.5 MPa, and 80°C for co-solvent percentage, pressure, and temperature, respectively.